Becoming a Tolerant Muslim: Study of Dayak Converts - Muslimah; Hamdanah; Syar’i, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The religious tolerance of the Dayak people towards converts in their families in Central Kalimantan shows that there are several problems which must be faced. Because apart from being a minority (Dayak converts), the Dayak people still uphold the culture that has been passed down from generation to generation. This study is conducted using a field study with purposive sampling on converts who are identified based on the specified classification. Data are reviewed through literature studies and strengthened by in-depth interviews, then analyzed using the Nvivo 12 application. This study reveals that in practice, the Dayak people uphold religious principles while maintaining tolerance as a habitus which comes from historical products by producing collective individual practices or behavior. Furthermore, religious practices, tolerance, and habitus play an important role in the daily life of the Dayak community towards converts. This is because they respect each other's beliefs, customs, and culture through a system of mutual assistance between one another in social interactions and everyday life. An open attitude and mind are also the reason for harmony in respecting differences and maintaining goodness among others, but not forgetting religion and culture.